Analisis Faktor Perilaku Pernikahan Dini pada Remaja Tahun 2025 - Nur Fitri Ayu Pertiwi; Endah Dian Marlina; Lastri Indriyani (PT Nuansa Fajar Cemerlang, 2025)
Indonesia is the 37th country with early marriage in the world and Asia. Indonesia reached 1.5 million children engaged in early marriage. West Java ranked 3rd, and Cianjur ranked 2nd in West Java with 543 cases in 2020. This study aims to analyze the Analysis of Behavioral Factors of Early Marriage Among Adolescents in Pacet District, Cianjur Regency in 2025. This study was conducted using a qualitative approach with a phenomenological research design. The study was conducted with in-depth interviews to explore the behavioral factors of adolescents engaging in early marriage. The sampling method used a purposive sampling technique. This study was conducted from February to April 2025. This study discusses the analysis of behavioral factors of adolescents engaging in early marriage. Based on the results of in-depth interviews with five main informants and several supporting informants, it was found that adolescents engaging in early marriage were divided into two factors. External factors are the environment, customs and culture, family, economy, and social media. Internal factors of adolescents engaging in early marriage were also found, namely factors from themselves, adolescents' expectations of marriage, and changes after marriage. More intensive education and approaches are needed with teenagers and the community to address early marriage in Pacet District, Cianjur Regency.